(untitled) - Geogre, Eugen (New York, 1931)
This book is presentation about the anthropocentric significance of the experience of man (distance and perspective, the great ruins,..); The cosmocentric significance of the experience of man (th law of th world, the historical manifestations of the dualism of the world,...)
Keywords: Prehistoric peoples,Human beings,Civilization,Atlantis; Origin,History